INTRODUCTION - Mohd Azlan, Jayasilan; Mohamad Irwan, Aman; Indraneil, Das (UNIMAS Publisher, Sarawak Energy Berhad and Natural History Publications (Borneo) Sdn. Bhd., 2024)
Ulu Baleh, located in the interior of Sarawak, Malaysian Borneo, and situated within the Rajang drainage area, is characterised by numerous small streams and larger tributaries. The area can be accessed traditionally only by long and tiring journeys upriver, and more recently, by land. While biodiversity declines are expected in logged tropical forests, those that are selectively logged appear to sustain significant biodiversity, especially the older regrowth forests. Ulu Baleh is, in fact, one of few areas in the Kapit region that can boast of old secondary as well as pristine rainforests. Vegetation surveys in the Baleh area have identified populations of hardwood trees (Eusideroxylon zwageri and Eusideroxylon melangangai), ferns (Dicranopteris sp.), nutrushes (Scleria purpurascens), fig trees (Ficus sp.) and blumes (Fragraea crassipes).